Prevalence of Biomass Use and its Effect on the Respiratory Health of Women Residing in Eastern Terai Region of Nepal - Adhikari, Puspanjali; Buddhacharya, Matina; Jha, Nilambar; Yadav, Deepak Kumar (Annapurna Journal of Health Sciences, 2023)
Introduction: Nearly one-third of the world’s population and three-quarters of rural households in developing countries still rely on unprocessed biomass fuel such as wood, cow-dung, and crop residues for cooking and heating. According to the World Health Organization, Indoor Air Pollution (IAP) from burning of biomass fuel has emerged as one of the top ten global threats to public health, as it accounts for 2.7 % of the global burden of disease. This study aimed to find out the prevalence of biomass use in the study area and the respiratory health problems associated with it in women. Methods: A descriptive cross-sectional study was conducted among women (18+ age) in a rural population (n = 415), exposed to biomass smoke. A semi-structured questionnaire was used along with an observation checklist. Data was entered in MS Excel and analysis was done using SPSS 11.5. Results: The prevalence of biomass use was 98.8%. The most common respiratory problems were cough (14.7 %) followed by phlegm (9.9%). Respiratory problems were significantly higher in people using leaves/straws as biomass fuel (p=0.034). Conclusion: Prevalence of respiratory symptoms is definitely higher among women using biomass smoke. There was no outlet for smoke in the kitchen among the rural women in our study thus provision for smoke vents is recommended.